AIDS Vaccine Trials: Ethical Ramifications and Policy Implications For Developing Countries - Doshi, Sucheta (Trinity Student Medical Journal, 2021)
This paper was originally presented at the 124th American Public Health Association Meeting in New York City as part of the International Health Section presentations, and has been updated to reflect current statistics